Dampak Sosial Ekonomi dari Pendirian Tempat Pemrosesan Akhir (TPA) dan Pemrosesan Sampah bagi Masyarakat Cipayung, Depok, Jawa Barat - Fika Sidqia Annidia; Maila D.H. Rahiem; Cut Dhien Nourwahida (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This study aimed to examine how the establishment of a Final Processing Site (TPA) and subsequent waste processing has influenced the local economy and social life of the Cipayung Village, Depok, West Java community. The methodological approach was qualitative and descriptive. Six residents, two TPA administrators, and the RT and RW heads of the area, participated in the study. The results of a thematic analysis of research data indicate that: 1) Environmental degradation caused by the TPA has an effect on people' daily routines; and 2) The existence of the TPA has created new employment prospects; 3) TPA administration facilitates the implementation of numerous activities, hence enhancing social interaction between people; 4) The presence of a TPA improves the socioeconomic well-being of community members. The local community, the TPA management and government must collaborate to safeguard their environment so that environmental issues generated by the establishment of the Cipayung TPA do not recur, and to maximize opportunities so that the Cipayung TPA becomes an innovation capable of promoting community welfare.